2004
DOI: 10.1080/14616730310001659566
|View full text |Cite
|
Sign up to set email alerts
|

Continuity, discontinuity, and coherence in attachment from infancy to late adolescence: Sequelae of organization and disorganization

Abstract: This longitudinal study examines continuity and discontinuity of attachment quality from infancy to late adolescence in a sample of 125 participants considered at birth to be at high-risk due to poverty. Strange Situations were conducted at 12 and 18 months; Adult Attachment Interviews were administered at age 19. Child and maternal characteristics and experiences and observational assessments of the families were explored as correlates of continuity and discontinuity in attachment. Contrary to findings of con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
110
2
3

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(121 citation statements)
references
References 27 publications
6
110
2
3
Order By: Relevance
“…According with previous studies (e.g., Hesse, 2008;Weinfield et al, 2004), our results confirm that the coherence in attachment narrative is a good indicator of secure and organized attachment representations, illustrating by moderate correlations between FFI latent factor and security and disorganization in both samples. Further studies could explore the relation between security, disorganization and the psychological adjustment of adopted adolescents, which could be done within the context of AAARN.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…According with previous studies (e.g., Hesse, 2008;Weinfield et al, 2004), our results confirm that the coherence in attachment narrative is a good indicator of secure and organized attachment representations, illustrating by moderate correlations between FFI latent factor and security and disorganization in both samples. Further studies could explore the relation between security, disorganization and the psychological adjustment of adopted adolescents, which could be done within the context of AAARN.…”
Section: Discussionsupporting
confidence: 76%
“…Furthermore, many attachment studies have concluded that the coherence is a central marker of both security and organization in both childhood (e.g., Weinfield, Whaley, & Egeland, 2004) and adulthood (e.g., Hesse, 2008). While security has always been related to psychological adjustment (e.g., Sroufe, 2005), nowadays disorganization is also considered to play an important role in psychological well-being (Green & Goldwyn, 2002).…”
mentioning
confidence: 99%
“…Importantly, research demonstrates that the quality of attachment varies according to the nature of parentchild interactions, ruling out the notion that it is determined entirely by dispositional qualities of the infant and young child (45). Studies also show that while early attachment exerts substantial influence over later development, attachment status can change as a function of deterioration and stress in the parent-child relationship or improvements in the relationship (46,47).…”
Section: What Is Attachment?mentioning
confidence: 99%
“…Moss et al, 2004) and abnormalities have been noted well into adolescence (e.g. Weinfield et al, 2004).…”
Section: Linking To the Private World Of Othersmentioning
confidence: 99%